Exploration and characterization of exopolysaccharide-producing bacteria from soil in West Kalimantan for improving sandy soil aggregation - Nasrul Harahap; Dwi Andreas Santosa; Nuni Gofar (Brawijaya University, 2018)
Exopolysaccharide (EPS) is a complex mix of macro-molecular electrolyte contained in the outer cells of bacteria excreted as mucus and has a role in soil aggregation. This study aims to obtain bacteria that have a high potential for exopolysaccharide-producing bacteria. A total of 112 isolates of exopolysaccharide-producing bacteria were isolated from rubber soil rhizosphere, secondary forest, and shrubs in PT. Hutan Ketapang Industri is the result of isolation on ATCC no.14 medium. Based on the observations of a morphological colony of these isolates, most of them similarities of color and shape but only 25 colonies are different isolates were obtained based on colony morphology. However, only 10 isolates formed a thick mucus or slimy when cultured on MacConcey agar. the results show that obtained three isolates of exopolysaccharide-producing bacteria have a higher value of the dry weight i.e. isolates RB292 (7.53 mg/mL) followed by RB51 (7.55 mg/mL), and RB241 (1.75 mg/mL) with 2% sucrose. Isolates RB51 and RB292 increasing significantly soil aggregate stability at 2% dosage of organic matter with soil aggregate stability index from 30.61% to 47.87% and 45.79%. Homology of the isolates with known bacteria i.e. isolate RB51 was 98.86% homolog with Klebsiella sp. LW-13, isolate RB241 was 98.65% homolog with Klebsiella pneumonia strain DSM 30104 and isolate RB292 was 98.83% homolog with Burkholderia anthina strain MYSP113